An Unusual Case of Metastatic Basal Cell Carcinoma of the Prostate: A Case Report and Literature Review - Dong, Shiqiang; Liu, Qing; Xu, Zihan; Wang, Haitao (Frontiers in Oncology, 2020)
Background: Primary basal cell carcinoma (BCC) is a rare prostate cancer. Currently, a standard treatment regime for BCC of the prostate is lacking and most patients have a poor prognosis. We reported on a patient with BCC of the prostate whose cancer metastasized after undergoing a radical prostatectomy and whose prognosis improved after treatment with etoposide. Case Presentation: A 62-year-old male with a history of seminoma was admitted complaining of intermittent gross hematuria for 1 month. Following a prostate biopsy, the patient was diagnosed with BCC of the prostate and received radical prostatectomy and radiotherapy. Initially, the patient's symptoms improved; however, 2 years later, a chest computed tomography (CT) scan revealed lung nodules. The patient did not exhibit any symptoms of BCC of the prostate; however, pathological examination and immunohistochemical staining of the nodules confirmed metastatic BCC of the prostate. Chemotherapy with docetaxel and cisplatin was well-tolerated but did not slow disease progression. Next-generation sequencing revealed mutations in the ataxia telangiectasia-mutated (ATM), SWI/SNF-related matrix-associated actin-dependent regulator of chromatin subfamily b-member 1 (SMARCB1), and phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) genes. The patient did not receive targeted therapy owing to financial limitations and instead, etoposide was administered. A 9-month follow-up chest CT scan showed an 80% reduction in existing lung nodules and no new nodules had developed. Conclusion: Our patient, diagnosed with recurrent prostate BCC after receiving a radical prostatectomy, responded to treatment with etoposide. Radical prostatectomy and radiotherapy should remain first-line therapy; however, etoposide may be an alternative second-line therapy when other options are not available. Consensus regarding treatment plans, and the molecular mechanisms behind prostate BBC, must be elucidated.